(untitled) (Scottish Historical and Archaeological Internet Reports, 2020)
An investigation by Headland Archaeology (UK) Ltd took place in early 2013 in advance of a housing development at Ness Gap, Fortrose, Highland. The excavation revealed domestic activity dating from the Neolithic to the Early Bronze Age. A cluster of Neolithic pits provided insights into the development of agriculture in the area, with evidence for cereal production and the gathering of wild resources. The use of the site changed in the Bronze Age, with the landscape utilised for funerary practices, which were represented by stone cists and cremation burials, both urned and unurned. Analysis has further informed on the burial practices of the Bronze Age and added to our understanding of a unique peninsular landscape rich in prehistoric activity.